From Kant to Davidson : philosophy and the idea of the transcendental - Malpas, Jeff (Routledge studies in twentieth century philosophy, 2003)
Bringing together an international range of younger philosophers and established thinkers, this volume opens up the idea of the transcendental in philosophy.